Birds associated with pea crops (Pisum sativum L.) in Boyacá: contributions to the agroecological transition. - Sanchez Rojas, Edwin Fernando; Cardenas Cardenas, Maria Alejandra; Ramos Guarnizo, Erika Carmenza (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Agroecosystems are considered potential places for the conservation of biodiversity, where practices are carried out that link people in production processes with aspects that are not only technical and economic, but also social, biological and ecological. Therefore, the objective of the research was to characterize the avifauna associated with pea cultivation on a farm scale in the municipality of Samacá-Boyacá. The presence and abundance of the species was monitored for six years, in the months of greatest planting and production with some restrictions due to the situation of Covid-19. The trophic group to which each species belongs and the use it gives to the crop were recorded. 1451 records of birds belonging to 13 species distributed in 10 families were found, the frequency of species during the 24 sampling campaigns was constant, most feed on insects and small invertebrates, followed by fruits and seeds, in terms of the use of the crop food predominates. The interaction of birds with the crop evidences the need for the transition to undertake processes that allow peas to be produced in accordance with the biophysical characteristics of their ecosystems and to take the first steps in sustainable agriculture.